Stigma And Social Community Discrimination Against PLHIV In Ujung Bulu District - Nur Paelani; Aszrul AB; Andi Suswani (Comprehensive Health Care, 2022)
Human immunodeficiency virus, it can be interpreted that this virus can only infect humans, in other words these cells are able to reproduce on their own in the human body so that it can cause the human immune system to decrease. Acquired is defined as being transmitted from person to person, then immune means damaging the human immune system, while deficiency means reduced or decreased, a syndrome defined as people with AIDS who suffer from opportunistic infections and other infections. Stigma is an attribute, behavior, opinion, and negative response given to someone. Discrimination is a form of prejudice, or behavior, which distinguishes a person because he or she comes from a different social identity (religion, ethnicity, race, gender, and social orientation), because of this difference the person is treated badly. The purpose of this study is to find out the stigma and discrimination given by the community to PLWHA in the district. The tip of the kab. Bulukumba. This research method uses a qualitative research design with a phenomenological approach, six participants were selected according to the criteria and recorded during the interview process using a structured interview guide, then an interview transcript was made, and analyzed using thematic analysis. The results of this study obtained three themes, namely (1) Stigma of politeness (2) Stigma of structure (3) Discrimination. There are 3 themes found in this study. It is hoped that the community will be able to provide enthusiasm and support for both the patient and the patient's family.